A descriptive study on the factors that influence the reactions of individuals towards dissonance producing information. - Suyao, Delia Libo-on
The study on the veracity of Cognitive Dissonance Phenomena has been a subject to many researches each led to its expansion and numerous criticisms. One imperative area that emerged and is heavily criticized is the occurrence of the factors that led to dissonance., This is an attempt to re-validate the study of any social psychologists on the factors that led to cognitive dissonance theory. Cognitive Dissonance is an unpleasant state felt by a person whenever he receives information that is not in harmony or inconsistent to the opinions or attitudes he already holds to himself. And because it is unpleasant, the person is pressured to reduce or remove it either by: changing his attitudes so that they are now consistent to the attitudes he already holds to himself, changing his opinions to conform to the opinions he already holds to himself, acquiring new information related to his preconceived attitudes or opinions; and lastly, reducing the importance of the perceived information. This research would like to find out the factors that affect the reactions of individuals towards a dissonance producing information. This further aims to draw out the factor that has utmost effect to dissonance. Because the study does not deal with a cause and effect relationship, the variables identified are called as components: the communicator, the dissonance information, the channel, and the subject. The communicator is the researcher, the dissonant information is the communication gimmick of the abolition of the Bachelor of Arts in Broadast Communication degree program from the College of Arts and Sciences, UP in the Visayas (creatively crafted in a memorandum form). The channel is the memorandum letter. The subject is the BABC freshmen constituents. Purposive sampling is used to determine the respondents. The essays in the questionnaires filled out by the student-respondents and the behavior and questions raised by them during the induction of the communication intervention are the instruments designed to elicit the needed data.